2021
DOI: 10.1155/2021/6641510
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and Its Complications Exacerbate Development of Postpartum Depression: A Retrospective Cohort Study

Abstract: Background. Hypertensive disorders were proved to be associated with the development of depression. But it is unclear if pregnancy-induced hypertensive diseases, especially preeclampsia (PE), will affect postpartum moods. We aimed to determine the incidence rate of postpartum depression (PPD) in PE patients and comprehensively evaluate the association between PPD and PE, including its severity and complications. Methods. 425 participants including 130 PE mothers were enrolled in this retrospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
1
8
0
1
Order By: Relevance
“…To our knowledge, this is the first study to evaluate post-partum anxiety among HDP rats beyond the immediate post-partum period; however, clinical studies do report increases in depression and anxiety among women with HDP [ 8 , 42 , 43 ]. Furthermore, a study by Ying et al recently reported that PreE is an independent risk factor for the development of post-partum depression [ 6 ]. Thus, our findings support the link between HDP and changes in maternal mood contributing to the development of post-partum depression and/or anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study to evaluate post-partum anxiety among HDP rats beyond the immediate post-partum period; however, clinical studies do report increases in depression and anxiety among women with HDP [ 8 , 42 , 43 ]. Furthermore, a study by Ying et al recently reported that PreE is an independent risk factor for the development of post-partum depression [ 6 ]. Thus, our findings support the link between HDP and changes in maternal mood contributing to the development of post-partum depression and/or anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Women with a history of HDPs are at an increased risk of developing mood disorders, such as anxiety and depression [ 3 , 4 , 5 ]. Women with advanced HDPs, such as preeclampsia (PreE; new onset of high blood pressure after 20 weeks gestation) or HELLP (hemolysis, elevated liver enzyme, low platelet; considered to be a variant of PreE with more severe organ dysfunction and often life threatening) syndrome, are even more susceptible to these mood disorders and have been reported by some to have disturbances in cognitive function [ 6 , 7 , 8 ]. There have been several theories as to why women affected by HDPs are more susceptible to these changes, ranging from cerebral vascular dysfunction during pregnancy to long-term complications due to hypertension [ 9 , 10 ]; however, to date, none have been conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of women with PE experience perinatal or postpartum depression (61). Furthermore, it has been established that PE itself is a contributing factor to the development of post-partum depression, as highlighted by the study conducted by Ye et al (62).…”
Section: Increased Neuropsychiatric Symptoms In Pementioning
confidence: 99%
“…Previously, it was shown that there is a connection between depressive symptoms in early pregnancy and the mother's blood pressure during the first trimester (9). Other researchers have found that women with higher blood pressure in the third trimester tend to experience increased depression (5,62). There is a correlation between immune activation and oxidative and nitrosative stress, which has been linked to hypertension in individuals with depression (114).…”
Section: Associations Between Biomarkers and Severity Of Neuropsychia...mentioning
confidence: 99%
“…Postpartum depression is affecting about one in seven women [14]. With a global prevalence of PPD ranging from 3% to 38%, it impacts a significant number of mothers [15].…”
Section: Epidemiologymentioning
confidence: 99%